The role of social psychological processes in journalist's war and peace journalism attitudes - Yontucu, Huri; Husnu, Shenel; Ersoy, Metin (Sage Publications Inc, 2022)
Previous studies have shown factors including media ownership, socio-political censorship, ethnic division and, the lack of professional training as obstacles to practising Peace Journalism principles. This research explored how social psychological processes including intergroup contact and outgroup attitudes influence Peace Journalism attitudes. Turkish Cypriot (TC) and Greek Cypriot (GC) journalists living in the divided and conflicted island of Cyprus participated. Findings highlighted that quantity and quality of contact are positively correlated with positive feelings, common ingroup identity (CII) and Peace Journalism attitudes and negatively correlated with intergroup anxiety and War Journalism (WJ) attitudes. Results shed light on the benefits of positive and frequent contact among journalists and with outgroup members that enhance positive social psychological processes as well as Peace Journalism attitudes. By recognizing the importance of intergroup contact, Peace Journalism attitudes can be improved by decreasing social-psychological tensions and contribute to reconciliation, peace-building processes, and sustainable peace in conflicted societies.
Keywords: Peace journalism; war journalism; intergroup contact; common ingroup identity; outgroup attitudes; intergroup anxiety